2017
DOI: 10.1016/j.matdes.2016.11.106
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional thermal strain reduction by a tilting pillar architecture: Suspended Ge layers on Si (001)

Abstract: In this paper we present the exceptional thermal strain release provided by micrometric Si pillar arrays to Ge epitaxial patches suspended on them, for different pillar aspect ratios and patch sizes. By combining 3D and 2D Finite Element Method simulations, low-energy plasma-enhanced chemical vapor deposition on patterned Si substrates, μ-Raman, μ-photoluminescence and XRD measurements, we provide a quantitative and consistent picture of this effect with the patch sizes. Strain relaxation up to 85% of the valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…It has been further demonstrated that merging can also be obtained directly during growth (by raising the growth temperature) [21,31]. The suspended film is found [18] to still profit of the ability of the underlying pillars to release thermal strain by tilting. Despite displaying a good crystal quality, suspended films do display some defects, likely to be created during actual merging [21].…”
Section: Suspended Filmsmentioning
confidence: 95%
See 1 more Smart Citation
“…It has been further demonstrated that merging can also be obtained directly during growth (by raising the growth temperature) [21,31]. The suspended film is found [18] to still profit of the ability of the underlying pillars to release thermal strain by tilting. Despite displaying a good crystal quality, suspended films do display some defects, likely to be created during actual merging [21].…”
Section: Suspended Filmsmentioning
confidence: 95%
“…The vertical morphology offers two key advantages with respect to common 2D layers. On one hand, the free surface surrounding the crystals allows for very efficient relaxation of the thermal-stress field [15][16][17][18], therefore avoiding cracking. On the other hand, 60 • dislocations forming at the Ge/Si interface and laying on (111) planes, are confined to the bottom of the crystal only (no 60 • defect can reach the region located at a height h >1.4 b, where b is the Si pillar base width).…”
Section: Vertical Growth Of Ge/si By Lepecvdmentioning
confidence: 99%
“…The GaAs structure grown on the Ge suspended layer is a solid, uniform and continuum layer without voids or holes. The SEM measurements also show the absence of cracks in the Ge and GaAs layer, confirming that the thermal stress induced by the annealing and GaAs growth on the structure is released through the deformation of the Si pillars 31 .
Figure 3Cross-section SEM image of the whole structure of Sample A. It is possible to distinguish the separated Si pillars at the bottom, the merged Ge layer and the GaAs layer on the top.
…”
Section: Resultsmentioning
confidence: 56%
“…This Ge layer is free from TD and lattice matched with the GaAs. It can efficiently relax the thermal strain which can arise between the epilayer and Si substrate as a consequence of the growth procedure, thus avoiding the formation of cracks 31 . In addition, the three-dimensional modulated (hilly) surface of the suspended layer, owing to its intrinsic curvature, permits the formation, via annealing induced step bunching, of double-height steps on the Ge surface.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, a promising approach consists of growing the SiC film suspended on top of micrometer sized Si pillars, deeply etched into the substrate. It has been shown, indeed, that such an architecture is very effective in relieving strain by exploiting the additional degree of freedom of pillar tilting and rotation [7], allowing for a significant reduction of wafer bowing even with several μm thick SiC layers [8].…”
Section: Introductionmentioning
confidence: 99%